2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20188
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Student Performance on Computer-Based vs. Paper-Based Tests in a First-Year Engineering Course

Abstract: is a Master's student in the Biomedical Engineering Graduate program at The Ohio State University, graduating in May 2014. She graduated with her BS in Biomedical Engineering in Spring, 2013 from The Ohio State University. Meagan works as a Graduate Research Associate in the Injury Biomechanics Research Center and as a Graduate Teaching Associate with the Fundamentals of Engineering with Honors program in the Engineering Education Innovation Center (EEIC ). This is her fourth year as a teaching assistant in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…This paper compares the results of students who passed the quest on a computer and in real life. The analysis proved that the difference in results of two groups of students who participated in the IT championship is not significant, and confirms the results of the previous research [10,16]. However, the teenagers were mostly attracted to the 3D game.…”
Section: The Experiments Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This paper compares the results of students who passed the quest on a computer and in real life. The analysis proved that the difference in results of two groups of students who participated in the IT championship is not significant, and confirms the results of the previous research [10,16]. However, the teenagers were mostly attracted to the 3D game.…”
Section: The Experiments Resultssupporting
confidence: 83%
“…The specifics of the paper-based versus computer-based testing results application and comparison became extremely relevant during the COVID-19 pandemic when the majority of students switched to distance learning. In particular, this problem stands out for the high schools [9,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…It means that the examinees taking either the CBT or PBT version of FLE had similar achievement scores from the test. This finding supported some of the findings of the other previously published research findings (Garas, & Hassan, 2018;Hosseini et al, 2014;Ita et al, 2015;Karay et al, 2015;Khoshsima & Hashemi Toroujeni, 2017;Kim & Huynh, 2010;Kingston, 2009;Piaw, 2012;Mason et al, 2001) and contradicted to the findings of some other research findings (Choi, Kim, & Boo 2003;Chua & Don, 2013;Clariana, & Wallace, 2002;Hosseini et al, 2014;Maguire et al, 2010). It should be reminded here that, as mentioned by Hensley (2015), many researchers claimed an achievement difference between PBT and CBT attributed this difference to either technological issues or participant characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…There is a debate about which mode of assessment-computer-based or paper-based-is a better indicator of the achievement of learning outcomes (Noyes & Garland, 2009). However, there has been a significant number of studies that have shown very little significant difference in student performance between computer-and paper-based assessments (Barros, 2019;Choi et al, 2003;Ita et al, 2014;Khoshsima et al, n.d.;Nergiz & Seniz, 2013).…”
Section: Paper-based Testing (Pbt) Versus Computer-based Testing (Cbt)mentioning
confidence: 99%